Atmospheric aerosol particle size distribution from Lidar data based on the lognormal distribution mode. Issue 8 (August 2022) - Shi, Yuchen; Liu, Wenqing; Dong, Yunsheng; Zhao, Xuesong; Xiang, Yan; Zhang, Tianshu; Lv, Lihui
Abstract: Analysis of the atmospheric Aerosol Particle Size Distribution (APSD) retrieved from Light Detection and Ranging (Lidar) data is one of the popular fields in atmospheric remote sensing. An APSD retrieval method based on the lognormal particle size distribution, the Mie theory, and the Second Simulation of the Satellite Signal in the Solar Spectrum (6S) were studied. According to the 6S, this method divides the main body of the aerosols into four basic components and calculates the APSD from Lidar data and the optical and microphysical characteristics of these components. Numerical simulation and experimental observations reveal that this method can obtain the APSD for particle sizes of >0.15 μm in the different vertical layers with good reliability. Abstract : APSD; Lognormal particle size distribution; 6S; Lidar.